Intolerance before and after the 1517 Reformation and the Kenyan context: A theo-historical review - Gathogo, Julius Mutugi (Stellenbosch theological journal, 2020)
The article sets out to demonstrate that theo-social intolerance in both colonial and post-colonial Kenya, a phenomenon which reminisces other forms of intolerance during and after the 1517 reformation and the persecutions in the early Church, can be overcome. In Kenya, theo-social intolerance was evident when both the missionaries and the colonial authorities blocked any room for dialogue with the practitioners of African religion. It reached its climax when African Instituted Churches and their founded schools were closed down in 1952 by the colonial authorities. Intolerance also manifests itself through the tensions that are evident among Christians and Muslims, afro-Pentecostals versus mainline Churches and so on. As we mark over 500 years of reformation (1517-2019), are there lessons that can inform our theo-social discourses in the 21st century, especially in regard to theo-social tolerance? How can this Ubulwane/Unyama (beastly) behaviour be avoided in our future socio-ecclesial discourses? Despite borrowing broadly in order to build the case for religious tolerance, the article has cited the case of St Andrew’s Kabare, an Anglican Mission centre that was established in 1910, where Rev. Edmund Crawford demonstrated that dialogue between African culture and the Gospel has a positive impact on the society being evangelized.